A case of disseminated Legionnaires’ disease: The value of metagenome next-generation sequencing in the diagnosis of Legionnaires - Li, Shan; Jiang, Wei; Wang, Chun-Yao; Weng, Li; Du, Bin; Peng, Jin-Min (Frontiers in Medicine, 2022)
Background: Legionella rarely causes hospital-acquired pneumonia (HAP), although it is one of the most common pathogens of community-acquired pneumonia. Hospital-acquired Legionnaires' disease, mainly occurring in immunocompromised patients, is often delayed diagnosed with high mortality. The use of metagenome Next-Generation Sequencing (mNGS) method, which is fast and unbiased, allows for the early detection and identification of microorganisms using a culture-independent strategy. Case Report: A 52-year-old male, with a past medical history of Good’s syndrome, was admitted due to nephrotic syndrome. The patient developed severe pneumonia, rhabdomyolysis, and soft tissue infection after receiving immunosuppressive therapy. He did not respond well to empiric antibiotics and was eventually transferred to the medical intensive care unit because of acute respiratory failure and septic shock. The patient then underwent a comprehensive conventional microbiological screening in bronchoalveolar lavage fluid (BALF) and blood, and the results were all negative. As a last resort, mNGS of blood was performed. Extracellular cell-free and intracellular DNA fragments of legionella were detected in plasma and blood cell layer by mNGS, respectively. Subsequent positive results of polymerase chain reaction for Legionella in BALF and soft tissue specimens confirmed the diagnosis of disseminated legionnaires’ disease involving the lungs, soft tissue and blood stream. The patient’s condition improved promptly after a combination therapy of azithromycin and moxifloxacin. He was soon extubated and discharged from ICU with good recovery. Conclusion: Early recognition and diagnosis of disseminated Legionnaires' disease is challenging. The emergence and innovation of mNGS of blood has the potential to address this difficult clinical issue.